Integration of Automobile Mechatronics Technology into the Curriculum of Automobile Trades Programmes at the Technical Colleges in Nigeria - Ariyo Samson Oluwatimilehin; Udogu Kingsley Chimezia; Mamman Danladi (Britain International for Academic Research (BIAR) Publisher, 2021)
The purpose of this study was to examine the perceptions of automobile industries workshop craftsmen in relation to the integration of automobile mechatronics technology into the curriculum of automobile trade programmes in technical colleges in Nigeria. Three research questions guided the study. A survey research design was adopted for the study. The population for the study is 31 comprising 23 automobile industries workshop craftsmen who are currently working in automobile companies in Enugu state, and eight (8) automobile trades’ technical teachers in technical colleges in Enugu state. A structured questionnaire titled Instrument for Integrating Automobile Mechatronics Sub-systems (IIAMS) was used for data collection. Two experts from the Department of Industrial Technical Education, University of Nigeria, Nsukka, and one expert from Anambra Motor Manufacturing Company (ANAMCO) face validated the instrument. The reliability co-efficient of the instrument was found to be 0.87 using Cronbach Alpha. Data collected were analyzed using mean and standard deviation for the research questions, while t-test was used to test the null hypotheses. The results of the study indicate that that automobile craftsmen find difficulties in servicing some automobile mechatronics sub-systems, while 16 mechatronics sub-systems were agreed on to be integrated into the automobile curriculum. It was recommended that these mechatronics sub-systems should be integrated into technical college curriculum and that technical colleges should partner with automobile industries for effective training of craftsmen. The study will contribute positively to the understanding of automobile mechatronics technology, and how it can be integrated into the curriculum.